Feeling the heat: the effect of acute temperature changes on predator–prey interactions in coral reef fish. (16th March 2015) - Allan, Bridie J. M.; Domenici, Paolo; Munday, Phillip L.; McCormick, Mark I.
Abstract : Exposure to elevated temperatures significantly affects the predator-prey interactions of a common pair of reef fish. Predators exposed to elevated temperatures had increased maximum attack speeds. This coupled with decreasing prey escape speeds and distances led to increased predation rates with subsequent increases in capture success. Abstract : Recent studies demonstrate that the elevated temperatures predicted to occur by the end of the century can affect the physiological performance and behaviour of larval and juvenile fishes; however, little is known of the effect of these temperatures on ecological processes, such as predator–prey interactions. Here, we show that exposure to elevated temperatures significantly affected the predator–prey interactions of a pair of common reef fish, the planktivorous damselfish ( Pomacentrus wardi ) and the piscivorous dottyback ( Pseudochromis fuscus ). When predators exposed to elevated temperatures interacted with prey exposed in a similar manner, maximal attack speeds increased. This effect coupled with decreasing prey escape speeds and escape distances led to increased predation rates. Prey exposed to elevated temperatures also had decreased reaction distances and increased apparent looming threshold, suggesting that their sensory performance was affected. This occurred despite the increase in maximal attack speeds, which in other species has been shown to increase reaction distances. These results suggest that the escape performance of prey is sensitive to short-term increases in ambient temperature. As marine environments become more thermally variable in the future, our results demonstrate that some predators may become more successful, suggesting that there will be strong selection for the maintenance of maximal escape performance in prey. In the present era of rapid climate change, understanding how changes to individual performance influence the relationships between predators and their prey will be increasingly important in predicting the effects of climate change within ecosystems.